Recognition and management of early complications in CAR-T cell therapy and virus-specific T-lymphocyte therapy: a practical clinical reference - Marek Ussowicz; Ewa Jakubczyk; Tomasz Wróbel; Anna Czyż (Frontiers in Immunology, 2026)
Background Cellular immunotherapies—including chimeric antigen receptor T-cell (CAR-T) therapies and adoptive transfer of virus-specific T lymphocytes (VSTs) — have transformed the treatment of refractory hematological malignancies and post-transplant infectious complications. Eight products are currently authorized by the European Medicines Agency, encompassing seven autologous CAR-T products targeting CD19 or BCMA and tabelecleucel (Ebvallo), the first approved allogeneic off-the-shelf EBV-specific T-cell product for EBV-positive post-transplant lymphoproliferative disease. Despite their clinical efficacy, both modalities carry distinct early toxicity profiles that differ from conventional cytotoxic chemotherapy. Objective This review summarizes current recommendations for identifying, assessing, and treating early problems that can occur after CAR-T cell therapy and VST administration. Content CAR-T-specific complications discussed include cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), immune effector cell-associated hematotoxicity (ICAHT), and immune effector cell-associated HLH-like syndrome (IEC-HS). CRS is graded by ASTCT consensus criteria and managed with tocilizumab as first-line pharmacological therapy; steroid-refractory ICANS is most commonly treated with high-dose intravenous anakinra (up to 12 mg/kg/day) which is currently the most studied second-line option, although the supporting evidence remains largely observational. ICAHT is classified using the validated EHA/EBMT grading framework, separating early (day 0–30) and late (post-day 30) neutropenia by depth and duration, with management escalating from prophylactic G-CSF through hematopoietic cell boost to allogeneic HSCT as the ultimate option. For VSTs, the principal early complications are tumor flare reaction (in approximately 20% of tabelecleucel recipients), GVHD (below 5% with enriched products), acute infusion reactions, and low-grade CRS-like cytokine release. We summarize a differential diagnosis of overlapping syndromes, pediatric-specific adaptations, ICU escalation criteria, and a clinical monitoring schedule. Conclusions Internationally validated criteria grade the early complications of cellular immune effector therapies. Prompt recognition, early pharmacological intervention, and monitoring are essential to minimize non-relapse mortality. Expanding real-world experience and the integration of pre-treatment risk stratification tools will continue to refine evidence-based practice in this rapidly evolving field, ultimately leading to improved patient outcomes and reduced non-relapse mortality rates.